Case studies in adaptation: centring equity in global health education during the COVID-19 pandemic and beyond - Anna Pancheshnikov; C Nicholas Cuneo; Wilfredo R Matias; Rebeca Cázares-Adame; Abner Gamaliel Santos López; Ryan M Paxton; Chi Chiung Grace Chen (BMJ Global Health)
The COVID-19 pandemic disrupted all aspects of life globally and laid bare the pervasive inequities in access to education, employment, healthcare and economic security in both high-resource and low-resource settings. The global health field’s brittle attempts of addressing global health inequities, through efforts that in some cases have evoked the colonialist forces implicated in shaping these disparities, have been further challenged by the pandemic. COVID-19 has forced global health leaders to reimagine their field through innovation such as shifting the application of global health to a local focus, collaborating with community organisations and exploring virtual education technologies. We present four case studies illustrating this promising movement towards a more sustainable, ethical and equitable model of global health education practice.Case 1: trainees from the Massachusetts General Hospital Center for Global Health partnered with the Board of Health of Holyoke, a majority Latinx city with high poverty levels, to respond to the COVID-19 pandemic through research and intervention. Case 2: Prevencasa, a community health organisation in Tijuana, Mexico, providing healthcare to local underserved communities, shifted its focus from hosting international trainees to developing a multidisciplinary training programme for Mexican healthcare professionals. Case 3: the Johns Hopkins Global Health Leadership Program adapted its curriculum into a hybrid online and in-person migrant health and human rights elective, collaborating with local organisations. Case 4: a US-based and a Latin American-based organisation collaborated to create a longitudinal, virtual urogynaecology training programme with hybrid simulation practice to increase accessibility of procedural-based training.